Network Connections and Competitively Awarded Funding: The impacts of board network structures and status interlocks on nonprofit organizations' foundation grant acquisition. Issue 10 (25th November 2016) - Faulk, Lewis; Willems, Jurgen; McGinnis Johnson, Jasmine; Stewart, Amanda J.
Abstract: This analysis investigates whether nonprofit board connections with other nonprofit organizations and foundations explain organizational performance in earning foundation grants. Using a sample of 402 nonprofits and sixty-eight foundations in a single metropolitan area, we find that greater connectedness and status interlocks significantly influence organizations' ability to acquire resources. Network effects are partially mediated by the number of past grants received and a nonprofit's financial characteristics, including organizational size, fundraising expenses, and financial health. These findings, while supporting the role of networks in resource attainment, point to the complex and mutual relationships between organizational characteristics, network characteristics, and organizational performance.